Induksi dan Multiplikasi Kalus Eucalyptus sp. pada Berbagai Media Callus Induction Medium (CIM) Secara In Vitro - BARAELA EZRA WIJAYA; RINDANG DWIYANI; NI NYOMAN ARI MAYADEWI (Agrotrop : Journal on Agriculture Science, 2023)
Callus Induction and Multiplication of Eucalyptus sp. on Various Media Callus Induction Medium (CIM) In Vitro. Callus induction in vitro can be done by planting specific part of plant such as leaf, root, stem, etc in aseptic condition by using medium that contains 2,4-D, a plat regulator for promoting callus formation. One of the objectives of callus production in vitro is to form secondary metabolites, because eucalyptus is known as a producer of essential oils. This research is an initial study for in vitro production of secondary metabolites for further research. The aim of this study was to determine the most suitable callus induction medium for callus formation and callus multiplication for Eucalyptus grown in vitro. This research was designed as a Completely Randomized Design (CRD), five treatments, repeated five times. Woody Plant Medium (WPM) was used as the basic media. Several Callus induction Medium (CIM) were used as treatments, i.e. CIM1 = 1 ppm 2,4-D; CIM2 = 1,5 ppm 2,4-D; CIM3 = 2 ppm 2,4-D; CIM4 = 1 ppm NAA+1 ppm BAP; and CIM5 = 2 ppm NAA+ 2 ppm BAP. Variables observed were the time of curly leaf formation, time of the emerging callus, colour and texture of the callus, callus’s weight, callus surface area, the weight of callus after multiplication. The result showed that CIM4 and CIM5 had the fastest emerging callus (7 days after planting), CIM1 and CIM2 formed green and crumb texture of callus, CIM1 produced the highest of callus’s weight, and CIM2 resulted in the highest of callus’s surface area. In conclusion, the most suitable CIM for callus induction was CIM1, while for callus multiplication was CM2.